STRATEGIC MARKETING PRACTICES OF HIGH PERFORMING MALAYSIAN FIRMS - Faridah Hassan ,; Mohamed Sulaiman, (Asian Academy of Management Journal, 1996)
In today's extremely competitive world marketing effectiveness is not just a necessity, it is the prerequisite of business success. It was none other than Drucker who expressed the view that marketing is so basic to the business that it can hardly be looked at as a separate function. The final results of the business depend on how the customer sees the whole business. Subscribing to this viewpoint Kotler (1986) suggests that the number one challenge facing management is to develop, improve and implement competitive marketing strategies.